The relationship between fibularis muscle strength and lateral ankle sprain among high school netball players in Gauteng northern region. - Phokontsi, Lesley (My University, 2011)
Previous and current research findings contradict each other about whether a relationship exists between Fibularis Muscle Strength and Lateral Ankle Sprain. As it stands, there is no finality about the relationship between Fibularis Muscle Strength and Lateral Ankle Sprain. Hence, this study was aimed at establishing whether a relationship exists between Fibularis Muscle Strength and Lateral Ankle Sprain amongst high school net ball players in Gauteng Northern Region. If a relationship does exist and is well understood, further research may be recommended to come up with a rehabilitation protocol that may be used to prevent Lateral Ankle Sprain. In conducting this study, a longitudinal analytical approach was adopted where subjects were observed over a four months period of high school netball season in Gauteng Northern Region. This was the best design for this study because it enabled the researcher to examine the relationship between independent variables (Height, weight, age, balance and Fibularis Muscle Strength) and the dependent variable (Lateral Ankle Sprain). 100 randomly selected high school female netball players, ranging in age from 13 to 19 years (mean ± SD = 16.5 ±1.27), who represented schools in tournaments and games participated in this study. The researcher recorded baseline measurements of Fibularis Muscle Strength, balance, demographic characteristics (age, height and weight) for each of the 100 randomly selected subjects 2 weeks before the beginning of 2009 netball season. Subjects who sustained Lateral Ankle Sprain, during the netball season, filled in injury assessment forms which were collected by the researcher on every Monday until the end of the netball season. Data was then analysed using logistic regression analyses with testing done at 0.05 level of significance. The findings from this study revealed that 5% of the subjects reported Lateral Ankle Sprain. Balance and age were significantly associated with lateral ankle sprain (p<0.05) while Fibularis Muscle Strength, weight and height were not (p>0.05). Therefore, there was no relationship between Fibularis Muscle Strength and Lateral Ankle Sprain. Furthermore, Age and balance were identified as predictors of lateral ankle sprain.
Keywords: basekball players; netball players; sprained ankles